1995
DOI: 10.1021/jo00122a060
|View full text |Cite
|
Sign up to set email alerts
|

New synthetic applications of aryllead triacetates. N-arylation of azoles.

Abstract: Treatment of a variety of azoles or their anions with p-tolyllead triacetate in the presence of copper-(II) acetate afforded the corresponding IV-aryl derivatives, normally in excellent yields. Room temperature arylation of an aminobenzimidazole derivative was chemoselectively directed to the amino group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(58 citation statements)
references
References 3 publications
(6 reference statements)
1
55
0
Order By: Relevance
“…[104] However, Avendano and co-workers showed that imidazoles, pyrazoles, indazoles, and benzimidazoles were all suitable substrates for N-arylation with p-tolyllead triacetate (1.1-1.5 equiv) as the aryl donor with the copper catalyst [Cu(OAc) 2 ] in stoichiometric amounts (Scheme 96). [101][102] 1,2,4-Triazole was a poor substrate, but it was shown that the sodium salt reacted much better under the same conditions to afford only one regioisomer in high yield. In a chemoselectivity study, it was shown that the aminobenzimidazole 207 reacted solely at the N atom of the aniline group, although the product was only isolated in 50 % yield.…”
Section: Aryl Lead(iv) Triacetates As the Aryl Donor: C(aryl)-heteroamentioning
confidence: 99%
“…[104] However, Avendano and co-workers showed that imidazoles, pyrazoles, indazoles, and benzimidazoles were all suitable substrates for N-arylation with p-tolyllead triacetate (1.1-1.5 equiv) as the aryl donor with the copper catalyst [Cu(OAc) 2 ] in stoichiometric amounts (Scheme 96). [101][102] 1,2,4-Triazole was a poor substrate, but it was shown that the sodium salt reacted much better under the same conditions to afford only one regioisomer in high yield. In a chemoselectivity study, it was shown that the aminobenzimidazole 207 reacted solely at the N atom of the aniline group, although the product was only isolated in 50 % yield.…”
Section: Aryl Lead(iv) Triacetates As the Aryl Donor: C(aryl)-heteroamentioning
confidence: 99%
“…An efficient synthesis of b-hydroxyethyl-pyrazoles 364 and 365 from propylene and styrene oxide using Cs 2 CO 3 has been reported [316]. Through the use of Bi, B and Pb derivatives and copper-catalyzed cross-coupling reactions it is possible to make NÀC bonds between pyrazoles and unsubstituted phenyl rings [317][318][319][320], or between indazoles and aryl rings [321]. 8.5.1.1.5 N-Acylation (see also Section 8.6.4.2) N-Acetylated pyrazoles are obtained from N-unsubstituted pyrazoles by treatment with acetyl chloride (alone or in the presence of pyridine) or acetic anhydride.…”
Section: 51mentioning
confidence: 99%
“…[1][2][3][4] Although their synthesis has been accomplished successfully using aryllead triacetate, [5][6][7] triarylbismuth, 8 arylstannane, 9 arylsiloxanes 10 and arylboronic acid [11][12][13] reagents etc., these methods often employ expensive reagents or substrates requiring multistep syntheses, and some are highly toxic, which limits their utilization in synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%